Peasant Movements in Argentina and Brazil - Campos Motta, Renata (Contested extractivism, society and the state, 2017)
Contrary to expectations that the governments of the ‘pink wave’ in Argentina and Brazil would take a ‘left turn’ to address the demands of peasant movements in their struggle to bring about alternative agrarian policies, the structural conditions of these movements have continued to be fraught with violence and criminalisation. New mechanisms to demobilise their bases, including social conformism, have also played a role. Some institutional changes and policies have benefited peasants, yet these are marginal in comparison to the consolidation of agribusiness. The peasant movements have interpreted the political economy of commodity export and poverty reduction in terms of an alliance between ‘progressive’ governments and agrarian elites. They have concluded, therefore, that their main power lies in sustained mobilisation.